Cardiovascular consequences of completing a 160-km ultramarathon - Scott, J. M.; Esch, B. T. A.; Shave, R.; Warburton, D. E. R.; Gaze, D.; George, K. (Medicine & Science in Sports & Exercise, 2009)
Purposes: To comprehensively investigate the cardiovascular consequences of a 160-km ultramarathon using traditional echocardiography, speckle tracking imaging, cardiac biomarkers, and heart rate variability (HRV) and to examine the relationship between the changes in these variables.